APSIC Guidelines for environmental cleaning and decontamination. Issue 1 (December 2015) - Ling, Moi; Apisarnthanarak, Anucha; Thu, Le; Villanueva, Victoria; Pandjaitan, Costy; Yusof, Mohamad
Abstract This document is an executive summary of APSIC Guidelines for Environmental Cleaning and Decontamination. It describes best practices in routine cleaning and decontamination in healthcare facilities as well as in specific settings e.g. management of patients with isolation precautions, food preparation areas, construction and renovation, and following a flood. It recommends the implementation of environmental hygiene program to keep the environment safe for patients, staff and visitors visiting a healthcare facility. Objective assessment of cleanliness and quality is an essential component of this program as a method for identifying quality improvement opportunities. Recommendations for safe handling of linen and bedding; as well as occupational health and safety issues are included in the guidelines. A training program is vital to ensure consistent adherence to best practices.